Web based e-portal for friday wisdom - Nor Zulaila, Razali (2009)
With the vast development of various technologies, learning today is no longer confined to a group discussion with lecture delivery as the only method of conveying knowledge,rather,an electronic means of learning has continued to evolve.A portal,which facilitates education using communications networks,has made learning possible from anywhere at anytime using the Internet,wide area networks or local area networks.Web based e-portal for Friday Wisdom (E-Fridom) either hybrid or non-hybrid demands students'commitment as a significant factor to ensure that the objectives of a learning portal could be achieved. The ultimate aim of a paperless world may be farfetched at present but as a means of information dissemination towards an e-forum discussion supports e-learning due to the fact that students'online participation could be more effective compared to manual discussion.This project develops the web portal that will change the manual system that had been used by student before.In manual system, students have to sign attendance in a paper,due to the limitation of the program that be held in an hour, student cannot ask more questions.Hence,student cannot exchange information together.E-Fridom will computerize them in the effective manner using suitable technology,tool, method and technique.Therefore,this project will develop interactive portal for UMP students.